2021
DOI: 10.1155/2021/6641689
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Sosiho-Tang, a Traditional Herbal Formula, on Acute Lung Injury in LPS-Sensitized Mice and -Raw 264.7 Cells

Abstract: Acute lung injury (ALI) is a series of syndromes with persistent inflammation and abnormally increased vascular permeability. Sosiho-tang (SSHT), a traditional herbal formula consisting of a mixture of seven herbs, has been used to treat allergic reactions and chronic hepatitis disease in East Asia. In this study, we determined whether SSHT has an inhibitory effect against lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in mice. 0.05, 0.55, and 5.55 mg/kg of SSHT were orally administered to C57BL/6J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…They concluded that SSHT inhibited nitric oxide, immune response cytokines, and NF-κB through the dephosphorylation of the MAPK pathway in LPS-induced RAW264.7 cells. Choi et al also employed RAW 264.7 cells in LPSinduced model, and found a similar inhibition of pro-inflammatory cytokines, such as IL-6 and TNF-α, via pretreatment or co-treatment with SSHT [50]. In a study of acute pancreatitis, Zhan et al used LPS-stimulated rat pancreatic AR42J cells, and SSHT played an important role in the treatment of acute pancreatitis by acting on the key genes of MAPK3, IL-6, and TP53, which were associated with inflammation [51].…”
Section: In Vitro Studies On Sshtmentioning
confidence: 87%
“…They concluded that SSHT inhibited nitric oxide, immune response cytokines, and NF-κB through the dephosphorylation of the MAPK pathway in LPS-induced RAW264.7 cells. Choi et al also employed RAW 264.7 cells in LPSinduced model, and found a similar inhibition of pro-inflammatory cytokines, such as IL-6 and TNF-α, via pretreatment or co-treatment with SSHT [50]. In a study of acute pancreatitis, Zhan et al used LPS-stimulated rat pancreatic AR42J cells, and SSHT played an important role in the treatment of acute pancreatitis by acting on the key genes of MAPK3, IL-6, and TP53, which were associated with inflammation [51].…”
Section: In Vitro Studies On Sshtmentioning
confidence: 87%